2007
DOI: 10.1002/pts.786
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady‐ and steady‐state gas permeation through active packaging walls

Abstract: Steady-and unsteady-state gas permeation rates through packaging walls containing active (scavenger) materials are determined as functions of the system's physical parameters and the scavenger load. With the simplifying assumptions of constant scavenger concentration and first-order reaction kinetics, steady-state analysis shows that there is a minimum quantity of scavenger that must be added to the packaging wall if any reduction of gas permeation is to be achieved. Unsteady-state studies have established the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…This correction would result in larger˚val-ues for both Cu 2+ experiments than for all 1,2,4-TCB experiments. A large˚explains the lag time-lengthening behavior observed in Cu 2+ experiments [46].…”
Section: Factors Controlling Cu 2+ Sorption and Diffusion In Pvamentioning
confidence: 98%
See 1 more Smart Citation
“…This correction would result in larger˚val-ues for both Cu 2+ experiments than for all 1,2,4-TCB experiments. A large˚explains the lag time-lengthening behavior observed in Cu 2+ experiments [46].…”
Section: Factors Controlling Cu 2+ Sorption and Diffusion In Pvamentioning
confidence: 98%
“…4a is also considered. Typically, Damköhler numbers should be above 0.01 for any visible barrier improvements with the addition of an active scavenger and above 100 to show increased lag time-type behavior [46]. The values in Table 2 are relative numbers based on relative kinetic data, however, so the absolute values of˚reported in Table 2 cannot be compared to this theoretical range.…”
Section: Factors Controlling 124-tcb Sorption and Diffusion In Pvamentioning
confidence: 98%
“…The transient response time is also negligible, for a typical bottle being of the order of a day or two at the most, 12 thereby yielding the well-known result of a linear concentration profi le across the wall, and a corresponding gas fl ux given by:…”
Section: Bottles Of Pure Petmentioning
confidence: 99%
“…where l is the axial draw ratio. It has been shown that transient periods also remain small in these cases, 12 so that Equation 8 can still be used, but with the appropriately modifi ed permeability value, as given by Equation 11.…”
Section: Bottles Of Pet Plus a Passive Materialsmentioning
confidence: 99%
See 1 more Smart Citation